Quiet struggles: Migrant farmworkers, informal labor, and everyday resistance in Canada. (April 2020) - Cohen, Amy; Hjalmarson, Elise
Utilizing James C. Scott's germinal concept of everyday resistance, we examine the subtle, daily acts of resistance carried out by Mexican and Jamaican migrant farmworkers in the Okanagan Valley, British Columbia. We argue that despite finding themselves in situations of formidable constraint, migrant farmworkers utilize a variety of "weapons of the weak" that undermine the strict regulation of their employment by employers and state authorities. We also argue that everyday forms of resistance are important political acts and as such, they warrant inclusion in scholarly examinations. Indeed, by reading these methods neither as "real" resistance nor as political, we risk reproducing the same systems of power that de-legitimize the actions, agency, and political consciousness of subaltern and oppressed peoples. After a brief discussion on the concept of everyday resistance, we provide an overview of Canada's Seasonal Agricultural Worker Program (SAWP), establishing the conditions that drive migrant workers to resist and drawing connections between the regulatory framework of the SAWP, the informality of the agricultural sector, and migrant labor. Finally, we examine specific instances of resistance that we documented over 3 recent years through ethnographic fieldwork and as community organizers with a grassroots migrant justice organization. We assert the importance of situating migrants' everyday acts of resistance at the center of conceptualizations of the broader movement for migrant justice in Canada and worldwide.